Orthogonal Catalysis for an Enantioselective Domino Inverse‐Electron Demand Diels−Alder/Substitution Reaction. Issue 5 (7th December 2021) - Beeck, Sebastian; Ahles, Sebastian; Wegner, Hermann A.
Abstract: An enantioselective domino process for the synthesis of substituted 1, 2‐dihydronaphthalenes has been developed by the combination of chiral amines and a bidentate Lewis acid in an orthogonal catalysis. This new method is based on an inverse electron‐demand Diels−Alder and a subsequent group exchange reaction. An enamine is generated in situ from an aldehyde and a chiral secondary amine catalyst that reacts with phthalazine, activated by the coordination to a bidentate Lewis acid catalyst. The absolute configuration of the product is controlled by chiral information provided by the amine. The formed ortho ‐quinodimethane intermediate is then transformed via a group exchange reaction with thiols. The new method shows a broad scope and tolerates a wide range of functional groups with enantiomeric ratios up to 91 : 9. All‐in‐all, this enantioselective synthesis tool provides an easy access to complex 1, 2‐dihydronaphthalenes starting from readily available phthalazine, aldehydes and thiols in a combinatorial way. Abstract : Thioether substituted trans ‐1, 2‐dihydronaphthalines have been accessed through a novel enantioselective domino process. Lewis acid activation and organocatalysis were combined to generate the products from readily available substances. A new chiral amine catalyst ensures high enantiomeric ratios. Both enantiomers of the product can be derived and the configuration on the newly generated stereo centers were unambiguously related to the chirality of the amine.